2022
DOI: 10.1038/s41598-021-04023-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with inosine-5′-monophosphate improves the functional, energetic, and antioxidant status of liver and muscle growth in pigs

Abstract: Inosine 5′-monophosphate (5′-IMP) is an essential nucleotide for de novo nucleotide biosynthesis and metabolism of energy, proteins, and antioxidants. Nucleotides are conditionally essential, as they cannot be produced sufficiently rapidly to meet the needs of the body in situations of oxidative stress or rapid muscle growth. A deficient intake of nucleotides can result in decreased ATP and GTP synthesis and impaired metabolism. We demonstrated that supplementation of finishing pig diets with 5′-IMP reduces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…IMP has been linked to the energetic metabolism of hepatocytes, especially AMP synthesis, and the energy metabolism of mitochondria. Dietary supplementation with IMP enhances hepatic antioxidant activity by attenuating mitochondrial uncoupling activity and damage to hepatocytes [48]. Thus, we suggest that the hybrid model of NASH abruptly decreases Nrf2 protein levels in both strains by distinct underlying mechanisms.…”
Section: Discussionmentioning
confidence: 74%
“…IMP has been linked to the energetic metabolism of hepatocytes, especially AMP synthesis, and the energy metabolism of mitochondria. Dietary supplementation with IMP enhances hepatic antioxidant activity by attenuating mitochondrial uncoupling activity and damage to hepatocytes [48]. Thus, we suggest that the hybrid model of NASH abruptly decreases Nrf2 protein levels in both strains by distinct underlying mechanisms.…”
Section: Discussionmentioning
confidence: 74%
“…IMP can be converted to adenosine diphosphate or guanosine-5′-diphosphate and then to adenosine triphosphate or guanosine trisphosphate ( 39 ). IMP is an important indicator of meat quality and freshness in animals ( 40 , 41 ). However, the role of IMP in humans is rarely mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…IMP content has been regarded as an important index to measure meat flavor in the world (D. Li et al, 2017 ; Takayanagi et al, 2020 ). Studies have shown that IMP is a major contributor to meat flavor in livestock, poultry and fish muscle, and its ability to increase umami taste is tens of times stronger than that of glutamate ( Bonagurio et al, 2022 ). Therefore, the flavor of livestock, poultry and fish mainly depends on the content of IMP in meat.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, how to improve the meat quality of cultured fish, make it more delicious and improve its market economic value is a hot issue in aquaculture research. Umami is an important indicator to measure the quality of aquatic products, among which inosine monophosphate (IMP) is the main umami substance in aquatic products, and IMP is an important factor to affect the umami quality of fish and consumer preference ( Hu et al, 2015 ; Bonagurio et al, 2022 ). The enzyme encoded by AMPD1 gene is the key enzyme that catalyzed the cleavage of adenosine monophosphate (AMP) to generate IMP, that is, AMPD1 gene plays a decisive role in the formation of IMP( Norman et al, 1998 ; Norman et al, 2001 ; Thebault et al, 2010 ; Hu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%